UPAYA MIGRANT CARE DALAM MEMBANTU PENANGANAN KASUS PERDAGANGAN MANUSIA OLEH PERUSAHAAN ICLEAN SERVICES DI MALAYSIA TAHUN 2019-2020 - Najla Ramadhanthi Yuristiannisa (2023)
Human trafficking is caused by economic pressures that are motivated by poverty and inadequate employment at the place of origin, so that a person has to leave the area of origin to get better economic opportunities. One of the main destination countries for Indonesian Migrant Workers (PMI) is Malaysia. But instead of getting a decent job, Indonesian Migrant Workers (PMI) have instead become victims of human trafficking in Malaysia, especially at PT. IClean Services. This case started with a complaint made to Migrant CARE Malaysia by eight (8) Indonesian migrant workers, especially women who worked at the company. The complaint revealed various breaches of employment contracts by the company. However, there was no firm action from the Government, both from Malaysia and Indonesia, in handling the case. This is the problem in this study due to the lack of attention from the government so that Migrant CARE intervened to help deal with the case. This study aims to discuss cases of human trafficking that befell Indonesian Migrant Workers (PMI) in Malaysia, particularly at PT. IClean Services Malaysia using the concept of human trafficking and the theory of Non-Governmental Organizations (NGOs). The method used is qualitative using primary data sources and secondary data. The sampling technique was carried out by purposive sampling. This researcher uses four stages of data analysis according to Miles & Huberman, namely data collection, data reduction, data presentation, and withdrawal or verification by data triangulation. The final results of this study indicate that the government needs to involve other stakeholders to help deal with cases of human trafficking. One of the non-governmental organizations handling the case is Migrant CARE as an institution engaged in the issue of protecting Indonesian Migrant Workers abroad.